2021
DOI: 10.3390/toxins13020156
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation Effects of Bentonite and Yeast Cell Wall Binders on AFB1, DON, and OTA Induced Changes in Laying Hen Performance, Egg Quality, and Health

Abstract: The objective of this study was to evaluate the efficacy of mycotoxin binders in reducing the adverse effects of co-occurring dietary aflatoxin B1 (AFB1), deoxynivalenol (DON) and ochratoxin A (OTA) on laying hens. Three hundred and sixty 26-week-old Roman laying hens were randomly allocated into four experimental groups with 10 replicates of nine birds each. The four groups received either a basal diet (BD; Control), a BD supplemented with 0.15 mg/kg AFB1 + 1.5 mg/kg DON + 0.12 mg/kg OTA (Toxins), a BD + Toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
5
10
1
Order By: Relevance
“…However, inclusion of XL to the diet could increase the mRNA expression level of claudin-1 and Occludin , decrease claudin-2 expression in broilers jejunum, indicating that XL can maintain the integrity of the tight junction of broilers' intestinal tract, and thus enhance the function of intestinal mucosal barrier in broilers to some extent. This result displays similar effect of dietary XL on laying hens ( Zhao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, inclusion of XL to the diet could increase the mRNA expression level of claudin-1 and Occludin , decrease claudin-2 expression in broilers jejunum, indicating that XL can maintain the integrity of the tight junction of broilers' intestinal tract, and thus enhance the function of intestinal mucosal barrier in broilers to some extent. This result displays similar effect of dietary XL on laying hens ( Zhao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…These results were inconsistent with some previous study ( Liu et al, 2018a ), but in accordance with others ( Morales-López et al, 2009 ; Liu et al, 2018c ). The different effects of adsorbents on production performance may be largely attributable to inclusion concentration of binders and AFB 1 , varied quality, and poultry breeds ( Zhao et al, 2010 , 2021 ; Liu et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the application of binders' adsorption of mycotoxins from the gastrointestinal tract of animals is the most effective way in practice [40,41]. While development of novel microorganisms or their enzymes used to biodegradation of the mycotoxins is also a promising approach [39,40,42].…”
Section: Occurrence Of Don In Feedsmentioning
confidence: 99%
“…Montmorillonite’s application as a metal ion carrier has attracted widespread interest. Some researchers have found that copper carried in montmorillonite has antibacterial effects [ 12 ]. Our research group uses ion-exchange reactions to synthesize copper-loaded montmorillonite (MMT).…”
Section: Introductionmentioning
confidence: 99%